Toxic effects of polystyrene microplastics on the intestine of Amphioctopus fangsiao (Mollusca: Cephalopoda): From physiological responses to underlying molecular mechanisms. (December 2022) - Zheng, Jian; Li, Congjun; Zheng, Xiaodong
Abstract: Microplastics are broadly used and among the most studied environmental pollutants due to their potential impacts on organisms and human health. Amphioctopus fangsiao (Cephalopoda: Octopodidae) is an important commercial species in the Pacific Northwest and is very popular among consumers owing to its rich nutritional value and fresh flavor. However, the toxic effects of microplastic exposure on A. fangsiao, including phenotypical effect and underlying molecular mechanism, remain limited. In this study, the octopus A. fangsiao were exposed to microplastics (polystyrene microplastics, Micro-PS) at concentrations of 100 and 1000 μg/L for 21 days, and then the physiological response, histopathological analysis, biomarkers of oxidative stress and glycolipid metabolism, microbiome perturbations and transcriptomic profiles in the intestines were performed. Results demonstrated that Micro-PS exposure had distinct adverse effects on the food intake of A. fangsiao . Histological analysis revealed that Micro-PS exposure has resulted in histopathological damage, thus causing early inflammation of the intestine. Oxidative stresses, metabolic disorders and microbiome perturbations were also detected in the intestine of A. fangsiao based on physiological biomarkers and microbiome analyses. Moreover, transcriptome analysis detected the differentially expressed genes (DEGs) and significantly enriched KEGG pathways in response to oxidative stress, glycolipid metabolism, DNA damage and transmembrane transport of intestinal cells, revealing distinct toxic effects at the molecular level. In summary, Micro-PS exposure has a strong impact on the intestines of A. fangsiao . For the first time, this study uses multiple approaches based on the physiological and biochemical response as well as transcriptional regulation analysis. The first assessment of the toxic impact of this species under Micro-PS exposure is also reported. Graphical abstract: Image 1 Highlights: Microplastic exposure caused intestinal toxicity damage of Amphioctopus fangsiao . this study, the octopus A. fangsiao were exposed to microplastics (polystyrene microplastics, Micro-PS) at concentrations of 100 and 1000 μg/L for 21 days, and then the physiological response, histopathological analysis, biomarkers of oxidative stress and glycolipid metabolism, microbiome perturbations and transcriptomic profiles in the intestines were performed. The first assessment of the toxic impact of microplastic on octopus is reported. Multiple approaches were used to perform the comprehensive analysis.